Automatic analysis of eyelid movement in de-novo Parkinson's disease - Kälble, Louis; Tykalova, Tereza; Zogala, David; Dusek, Petr; Rusz, Jan; Novotny, Michal (NPJ Parkinson's disease, 2025)
This study presents an automated, objective method for eyelid movement assessment in de-novo Parkinson's disease(PD) using a one-dimensional camera setup during monologue. These measurements were related to Dopamine Transporter Single Photon Emission Tomography and clinical scores. State-of-the-art computer-vision technologies and deep-learning neural networks were utilized to measure fourteen eyelid movement markers describing blinking and eyelid kinematics. Video-recordings were collected from a total of 120 de-novo patients with PD and 55 healthy controls. Abnormal blinking was present in 38% of PD, indicated by a reduced blink rate (p < 0.001), an increased inter-blink interval (p < 0.001), and an increased rigidity of the palpebral aperture (p < 0.001). The classification experiment reached an area under the curve of 0.81 on a blinded test set. The blink rate correlated with the loss of nigral dopaminergic neurons (r = 0.35, p < 0.001). These findings suggest eyelid movement markers as strong reflections of striatal dopaminergic activity levels, underscoring the method's potential as a reliable early PD biomarker.